Índices de qualidade do solo e de sustentabilidade no contexto do pagamento por serviços ambientais, Sub-bacia das Posses, Extrema, MG - Gomes, Fábio José (2017)
In order to achieve a balance between the use of environmental resources and the preservation of ecosystem services, it is necessary to know the environment and its current level of sustainability. The evaluation of soil quality and the sustainability of a sub-basin may prove to be important tools for managing areas of social and environmental interest. The study area corresponds to the hydrographic Posses sub-basin, located in the Extrema county, Minas Gerais State. The study aim is contribute to scientific knowledge regarding soil quality and the sustainability of the Water Conservation Project in the sub-basin. The dissertation was divided into three articles. The first article is about two methods of selection of indicators and two different methodologies of obtaining the soil quality index in relation to water erosion and water recharge were evaluated and compared. In the second article, a survey of social, economic and environmental indicators was carried out with the purpose of serving as a subsidy to the decision-makers of the municipality and the Water Conservation Project in the sub-basin. Finally, the third article evaluated the sustainability index of the Posses Sub-basin, based on indicators of the environmental, social, economic and institutional dimensions. For the elaboration of this study 127 soil samples of the superficial layer (0-0.20 m) distributed by the sub-basin were used to calculate of soil quality indexes in the first article. The indicators raised in the second article and the sustainability index in the third article had a large part of their data from interviews with the sub-basin's rural owners. Through these interviews were identified and characterized the main social, economic, institutional and environmental aspects of the area. The results showed that the Principal Components Analysis was an efficient tool to decrease data size used to calculate soil quality index, contributing to the reduction of time and cost of laboratory analysis, and the Nemoro Quality Index calculated from the Minimum Data Set was the most recommended models for the region. Regarding the indicators raised in the sub-basin, there was a low level of schooling of the adult population (5.37 years of schooling), and that all rural producers in the Posses Sub-basin are small farmers and high social inequality was observed. The environmental indicators raised have shown good environmental quality, although some aspects need to improved, such as level planting in all crops and the replacement of cesspool by septic tanks or by evapotranspiration tank, to avoid soil and underground water contamination. Assessing the sustainability of the sub-basin, we identified the indicators that obtained the worst performances and that should receive special attention from the Water Conservation Project, which are area with native forest, land use agroforestry and technical assistance. The study concludes that the Nemoro Quality Index calculated from the Minimum Data Set presented an excellent coefficient of determination with water losses. Making it possible to use the decision on Payments for Environmental Services in soil and water conservation by the Water Conservation Project. An alternative to be adopted to improve the sustainability level of the site is the creation of a special modality of Payment for Environmental Services aiming to provide technical assistance, rather than financial assistance, to the small owners of the sub-basin.